Komunikasi Antar Personal Dalam Pembiasaan Sopan Santun Di Pasraman Kota Mataram - Dewi, Ni Luh Made Larasanthi Komala; Widana, I Nyoman Murba; Patni R, Gusti Ayu Santi (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
This study focuses on three things, namely interpersonal communication in the habituation of polite manners, obstacles to the application of interpersonal communication in the habituation of polite manners and efforts to overcome obstacles to the application of interpersonal communication in the habituation of polite manners. The research method used is descriptive qualitative. From the results of data analysis it was found that in interpersonal communication in the habituation of polite manners at the Mataram City Pasraman, the acarya acted as a communicator who became a role model for the brahmacari in the habituation of polite manners at the Pasraman, the habituation of polite manners was internalized with structured and in-depth communication by the acarya to the brahmacari in implementation of learning at the Pasraman and intensive supervision by the manager and acarya in the habit of being polite to brahmacari at the Pasraman. Obstacles in the application of interpersonal communication in the habituation of politeness at the Mataram City Pasraman, namely, the influence of the environment and colleagues which has an impact on the difficulty of habituating brahmacari polite behavior, the influence of massive information technology developments influencing the behavior of polite brahmacari; and differences in brahmacari's ability to receive and respond to information conveyed by acarya. Efforts to overcome obstacles/obstacles in implementing interpersonal communication in the habituation of good manners in Pasrman, namely by building good cooperation between Pasraman managers, acarya and brahmacari parents so that brahmacari are able to receive, respond and implement information from acarya and Pasraman managers related to values courtesy.